Exploration of Mental Health in Individuals Engaging in Porn, Masturbate, and Orgasm (PMO) - Natasyah Febiyani Putri Loahandi; Arthur Huwae (Kuras Institute, 2026)
Porn, Masturbation, and Orgasm (PMO) behavior, which is increasingly prevalent in the digital era, is often used as an outlet for stress and loneliness. However, when done compulsively, it can cause negative impacts such as guilt, anxiety, and psychological well-being disorders. PMO is the activity of accessing pornographic content and masturbating to orgasm repeatedly, which can affect an individual's mental health. This study aims to explore the mental health of individuals who engage in PMO behavior. The approach used was qualitative with a phenomenological method to explore the personal experiences of five participants aged 17–27 who actively PMO consistently for more than six months and experienced psychological conflict or changes in mental state due to this behavior. Data were collected through in-depth interviews and analyzed using an interactive model. The results showed that all participants experienced various forms of psychological distress such as guilt, stress, anxiety, and inner conflict. However, aspects of psychological well-being were also found in the form of self-reflection, hope for change, and efforts to maintain social function. In conclusion, PMO behavior is closely related to complex mental health dynamics, where an individual's psychological well-being is greatly influenced by internal (personality, emotional regulation) and external (social stigma, interpersonal relationships) factors.